The Effectiveness Of Giving Beet Juice On Hb Levels In Third Trimester Pregnant Women At Budhi Asih Hospital In 2022 - Rahayu Khairiah; Dessi Butar-Butar (International Journal of Health and Pharmaceutical (IJHP), 2023)
Anemia in pregnancy is a condition of the mother with a hemoglobin level of less than 11.0 gram/dl. Anemia can be prevented by consuming a balanced nutritious diet with sufficient iron intake to meet the body's needs. Heme iron is found in green vegetables, red meat, egg yolks, raisins, prunes, liver, oysters and some fortified cereals. Knowing the effectiveness of giving beetroot juice on Hb levels in third trimester pregnant women at Budh Asih Hospital. The research design is Quasi Experimental, with the Pretest and Posttest Control Group design. The population in this study were third trimester pregnant women with a gestational age of 28-36 weeks in the working area of Budhi Asih Hospital. The sampling technique used purposive sampling with the number of respondents being 30 third trimester pregnant women. The statistical tests used are the Mann-Whitney and Wilcoxon tests. The mean level of anemia before being given beetroot juice therapy in the intervention group was 6.33 and 6.93 in the control group. The mean level of anemia after being given beetroot juice therapy in the intervention group was 11.20 and in the control group was 4.80. beetroot juice therapy is effective for reducing the level of anemia in third trimester pregnant women with p value = 0.000 ≤ 0.05. Giving beetroot juice is effective for increasing hemoglobin levels in third trimester pregnant women at Budhi Asih Hospital. It is hoped that midwives can provide regular education to mothers who experience anemia about the benefits of beetroot juice to increase hemoglobin levels in third trimester pregnant women. Reading List : 16 (Year 2013-2022).